A scale of development stages of the bean plant Phaseolus vulgaris. A summary for consultation - Fernández, F.; Gepts, Paul L. (International Center for Tropical Agriculture, 1984)
A scale of stages of development of the bean plant applicable to both determinate and indeterminate growth types is defined and described. It consists of 10 critical phenological steps comprised into 2 phases: one vegetative (V) and the other reproductive (R). The stages V 0 (germination), V 1 (emergence), V 2 (primary leaves), V 3 (1st trifoliate leaf), V 4 (3rd trifoliate leaf), R 5 (preflowering), R 6 (flowering), R 7 (pod development), R 8 (pod filling), and R 9 (maturity) are described. A phase or stage is superseded by the next as soon as the plant, when individually considered, or 50 percent of the plants of a plot or field, show the manifestation of the next stage. (CIAT)